Implementation of Senior High School Multicultural Education Curriculum in West Kalimantan - Kristianus Kristianus (Universitas Muhammadiyah Mataram, 2020)
The background of this research is the implementation of multicultural education that has been carried out by several Non Government Organizations (NGOs) in cooperation with the 22 high-level secondary schools in the range of 2005-2013. The author wants to know if the multicultural education is still being conducted and also wants to know the factors that affect the implementation of the multicultural education, especially on the aspects of the curriculum and teaching materials. The author conducts research on 12 (twelve) schools that have ever run the program. The study was conducted for two months with ethnographic methods. The author performs in-depth interviews alongside observations and library reviews. The results of this research show that the implementation of this program does not last according to the plan, although teenagers from schools studied in general are already aware of the multicultural education. Multicultural knowledge is still relatively low, but they want to learn the other ethnic culture. Other problems were found that the school did not continue the program because the curriculum of multicultural education and the existing teaching materials have not been perfected. Another important finding is that regional autonomy on the one hand can be an opportunity for schools to encourage multicultural education models but on the other hand to nourish identity politics. Both sides tend to be opposite, so it takes creative effort to connect them into the space of democracy and pluralism at school level. Violence in West Kalimantan can only be abolished when the community knows the root cause, then want and dare to face, deciding which chain that encourages violence is happening. If not then other violence will occur, and finally West Kalimantan will fall into the spiral of violence, as happened so far.